Metastatic intracranial solitary fibrous tumors/hemangiopericytomas: description of two cases with radically different behaviors and review of the literature. Issue 6 (July 2020) - Lavacchi, Daniele; Antonuzzo, Lorenzo; Briganti, Vittorio; Berti, Valentina; Abenavoli, Elisabetta Maria; Linguanti, Flavia; Messerini, Luca; Giaccone, Giuseppe
Abstract : Solitary fibrous tumor/hemangiopericytoma with primary tumor location in the central nervous system accounts for less than 1% of all central nervous system tumors. Despite the relatively indolent clinical course, extracranial metastases are reported in 28% of cases. In recent years, NAB2-STAT6 gene fusion has been recognized as the pathognomonic molecular feature of solitary fibrous tumor/hemangiopericytoma and STAT6 immunohistochemistry has been shown to be a sensitive and specific surrogate for the identification of the gene fusion in these patients. Here we report two cases of patients who experienced occurrence of diffuse extracranial metastases several years after successful surgery for an intracranial solitary fibrous tumor/hemangiopericytoma. In the first patient, the metastases had maintained similar histological features to the primary tumor; in contrast, in the second case, a dedifferentiation occurred with loss of expression of CD34 and Bcl-2. These different histological features were associated with radically different behaviors. Whereas the first case experienced an indolent course of the disease, the second patient had a rapid disease progression and deterioration of clinical conditions. The molecular imaging findings in these two cases and the role of functional imaging for tumor detection, disease staging and monitoring in this rare cancer are also discussed. Recurrences and metastases maintained high expression of somatostatin receptors confirmed by somatostatin receptor imaging in the first case. In contrast, in the second patient, the abrupt transition into a highly aggressive form was associated with the absence of somatostatin receptors at 111In Pentetreotide scan and intense hypermetabolism at 18F-FDG PET.